Microfluidic devices: The application in TME modeling and the potential in immunotherapy optimization - Li, Yuting; Fan, Honghong; Ding, Junli; Xu, Junying; Liu, Chaoying; Wang, Huiyu (Frontiers in Genetics, 2022)
With continued advances in tumor research, the crucial role of the tumor microenvironment (TME) in regulating tumor progression and influencing immunotherapy outcomes has been realized over the years. A series of studies devoted in enhance the response to immunotherapies through exploring efficient predictive biomarkers and new combination approaches. The microfluidic technology not only promoted the development of multi-omics analyses, but also enabled the recapitulation of TME in vitro microfluidic system, which made these devices attractive across studies for optimization of immunotherapy. Here, we reviewed the application of microfluidic systems in modeling TME and the potential of these devices in predicting and monitoring immunotherapy effects.